Spiritual Care Lab as an Experiential Teaching and Learning Model - Chung, Jaeyeon Lucy (Journal of pastoral theology, 2024)
This article examines the efficacy of the ‘Spiritual Care Lab’ as an experiential pedagogy for training caregivers, including chaplains, pastors, and spiritual providers. Within the realm of spiritual care, experiential pedagogy emphasizes real-life situations encountered in various care contexts, fostering active listening and compassionate skills. This study delves into the theoretical foundations of the Spiritual Care Lab, its methodology, and procedures. Drawing from the principles of experiential pedagogy, the Spiritual Care Lab integrates the intricate complexities of lived experiences, exploring the interwoven psychological, socio-cultural, and theological components. Supporting evidence includes student feedback data gathered in the fall of 2021. The objective of this article is to present an innovative approach to engaging in the Spiritual Care Lab, where spiritual care is embodied through listening, observing, speaking, and fostering communication among participants.